The simulated enterprise an essential factor in professional training for sustainable development - Dumitra Costa-Marcu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Practice Enterprise is a simulated model, which serves as the perfect solution for the current demand for new ways of teaching and learning. The new work place requirements were and are still incompatible with the training in which the student is passive recipient. In a business simulation students are required to actively participate in company activities and be responsible by playing a central role in all aspects of company management: accounting and the preparation of a statement, organizational, administrative and fiscal charges, domestic and international trade management, financing, investment banking relationships, the application of ICT, so on.
Keywords: 330; management; knowledge economy; human capital; employment; human resources; information technology; organizational culture